Penerapan Sistem Informasi Manajemen Nikah (SIMKAH) Dalam Meningkatkan Mutu Pelayanan Nikah Di Kua Kecamatan Ilir Barat I Kota Palembang - ., Alila Zahira Kusuma; ., Achmad Syarifuddin; ., Hasril Atieq Pohan (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
This research is entitled Application of Marriage Management Information Systems (SIMKAH) in Improving the Quality of Marriage Services at KUA, Ilir Barat 1 District, Palembang City. To improve quality in a service, service management is needed with the aim of being able to provide satisfaction with the services provided. This study aims to determine the application of the Marriage Management Information System (SIMKAH) in improving the quality of marriage services at the KUA, Ilir Barat 1 District, Palembang City. This study uses a qualitative approach, with data sources namely primary and secondary data. Data collection techniques used are interviews, observation and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The conclusions of this study are: (1) The application of SIMKAH used includes: Technology such as technology is adequate starting from computers, printing machines and Wi-Fi. Information such as data is stored safely because recorded data will be stored as a digital database. Humans are like human resources who are competent and professional. (2) Management of the services they use are: Physical Evidence such as the facilities provided are appropriate. Reliability as each employee has expertise in their respective fields. Catching Power is like a fast employee in responding to every complaint and providing a solution. Guarantees such as fast, accurate, timely, accountable. Empathy is like employees who are quick to respond when there are wedding parties that are still not clear and understand. (3) Supporting factors for the implementation of SIMKAH are infrastructure (sophisticated technology, Wi-Fi network), competent human resources and reward. As for the Inhibiting Factors, such as network disturbances which are sometimes less stable. For future researchers this scientific paper can be used as a reference for research in the same field.